Google Classroom in the English Language Teaching Learning during Pandemic Covid-19 - Hanifah Nuha Makarim; Dina Merris Maya Sari (Jurnal Pendidikan Bahasa, 2021)
In the context of preventing the transmission of covid-19, education at all levels has been transferred online. Google Classroom is a service created by Google for institutions education whose use has the full support of the Ministry of Education and Culture. After four times conduct English language lectures at STKIP PGRI SIDOARJO face-to-face, process it changes to an online system using Google Classroom. This research aims to know how to use the application in online classrooms, what advantages are there on the application in relation to English courses and what obstacles perceived by students and lecturers in using Google Classroom. Data were collected from 10 students obtained from the test instrument and questionnaire. The results showed the use of this online platform can motivate students to learn English. This matter can be seen with an increase in their language skills. In addition, students feel happy to learn with the application because the features available are easy to understand and also efficient in the use of time. However, Google Classroom also has weaknesses such as the display less interesting, file delivery that must be monitored and time settings that can still be changed. However, in general, the use of these applications can be a good choice as an online learning medium.In the context of preventing the transmission of covid-19, education at all levels has been transferred online. Google Classroom is a service created by Google for institutions education whose use has the full support of the Ministry of Education and Culture. After four times conduct English language lectures at STKIP PGRI SIDOARJO face-to-face, process it changes to an online system using Google Classroom. This research aims to know how to use the application in online classrooms, what advantages are there on the application in relation to English courses and what obstacles perceived by students and lecturers in using Google Classroom. Data were collected from 10 students obtained from the test instrument and questionnaire. The results showed the use of this online platform can motivate students to learn English. This matter can be seen with an increase in their language skills. In addition, students feel happy to learn with the application because the features available are easy to understand and also efficient in the use of time. However, Google Classroom also has weaknesses such as the display less interesting, file delivery that must be monitored and time settings that can still be changed. However, in general, the use of these applications can be a good choice as an online learning medium.Keywords: Google Classroom, Technology, English Language